Effect of retinoic acid on expression of receptor ccr9 and alpha 4 beta 7 integrin in alpaca blood leukocytes (Vicugna pacos) - Hermoza C., Eduardo (2018)
Effector T cells (CD4+ and CD8+) and memory cells can migrate to most extra lymphoid tissues in the body, but require the expression of specific homing receptors in T cells, α4β7 integrin and receptor chemokine CCR9. CD4+ or CD8+ circulating lymphocytes lack CCR9 and α4β7 receptors; however, these receptors are expressed upon reaching the intestinal mucosa. The aim of the study was to determine the effect of retinoic acid on the expression of CCR9 receptors and α4β7 integrin on alpaca lymphocytes (Vicugna pacos). An in vitro analysis of circulating alpaca blood sample was performed. The obtained leukocytes were placed in cell culture plates in minimal essential medium (MEM) supplemented with retinoic acid at concentrations of 10, 50 and 100 ìg/ml dissolved in DMSO. A control based on physiological serum was used. Cell culture plates were incubated for 12, 24 and 48 h at 37 °C with 5% CO2. Real-time PCR of the CCR9 receptor mRNA and α4β7 integrin and relative quantification with the 2-ΔΔCt method were performed. The maximum expressions for CCR9 were given at 48 h for concentrations of 10 and 100 μg/ml of retinoic acid and DMSO, and at 24 h for the concentration of 50 μg/ml. The control had much higher expressions compared to the doses of retinoic acid and DMSO. There was no expression for the α4β7 integrin.